Association between anthropometric, physical and demographic characteristics and performance among NCAA Division III swimmers - Edmond, S. L.; Milton, H. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: Anthropometric, physical and demographic characteristics have the potential to affect performance in competitive pool swimmers. METHODS: Study aimed were therefore to examine the effect of 26 anthropometric, physical and demographic characteristics on qualification for Nationals and swim times among both male and female collegiate swimmers in separate analyses. Swim times were determined by swimmers` best swim time for their best swim stroke as a percent of the top swim time among Division III collegiate swimmers during the 2017-2018 swim season. RESULTS: Lower body fat measured mid-season and a greater ratio of height to arm span were associated with qualifying for Nationals among females. For males, associations were present for older age, shorter left-hand length and larger left arm circumference; and qualifying for Nationals. In relation to percent of top swim times, there was an association between larger right-hand width and left foot length among males. None of the other associations achieved statistical significance. CONCLUSIONS: Owing to the large number of analyses performed and the resultant likelihood of type I errors as well as the small effect sizes in most statistically significant associations, study results suggest that collegiate swimmers should not be chosen for swim teams based on any of the non-modifiable anthropometric or physical characteristics that were measured in this study. Results suggest however, that swim speed times are decreased among female collegiate swimmers with lower body fat percent when measured mid-season.